Nonpharmacological interventions to treat physical frailty and sarcopenia in older patients: a systematic overview – the SENATOR Project ONTOP Series - Lozano-Montoya I (Dove Medical Press, 2017)
Isabel Lozano-Montoya,1,* Andrea Correa-Pérez,1,* Iosief Abraha,2 Roy L Soiza,3 Antonio Cherubini,2 Denis O’Mahony,4 Alfonso J Cruz-Jentoft1 1Servicio de Geriatría, Hospital Universitario Ramón y Cajal (IRYCIS), Madrid, Spain; 2Geriatrics and Geriatric Emergency Care, Italian National Research Center on Aging (IRCCS-INRCA), Ancona, Italy; 3Department of Medicine for the Elderly, National Health Service Grampian, Aberdeen, UK; 4Department of Medicine, University College Cork, Cork, Ireland *These authors contributed equally to this work Background: Physical frailty (PF) and sarcopenia are predictors of negative health outcomes such as falls, disability, hospitalization, and death. Some systematic reviews (SRs) have been published on different nonpharmacological treatments of frailty and sarcopenia using heterogeneous definitions of them. Objective: To critically appraise the evidence from SRs of the primary studies on nonpharmacological interventions to treat PF (defined by Fried’s frailty phenotype) and sarcopenia (defined by the EWGSOP) in older patients. Design: Overview of SRs and meta-analysis of comparative studies. Data sources: PubMed, Cochrane Database of Systematic Reviews, EMBASE, and CINAHL were searched in October 2015. Eligibility criteria for selecting studies: SRs that included at least one comparative study evaluating any nonpharmacological intervention to treat PF or sarcopenia in older patients in any health care setting. Any primary study described in these SRs with experimental design was included. Data extraction and management: Two reviewers independently screened titles, abstracts, and full-texts of articles. Quality assessment was carried out by using criteria from the Cochrane Collaboration and the GRADE working group. Results: Ten SRs with 5 primary studies satisfied the inclusion criteria. The most frequent interventions in the included studies were physical exercise (4) and nutritional supplementation (2). Muscle strength (MS; except for one study in a frail population) and physical performance (PP; except for another study in a frail population) improved with exercise and amino acid supplementation in frail and sarcopenic old adults. Falls and activities of daily living were assessed in two studies with opposite results. The overall quality of the evidence was low. Conclusion: This overview of SRs highlights the importance of exercise interventions with or without nutritional supplementation to improve the PP in community-dwelling patients aged >65 years with PF and sarcopenia. MS improved with multidisciplinary treatment and exercise interventions in this population. Keywords: review, exercise, nutrition, older adults